Pelatihan Geogebra Untuk Guru-Guru Sma Di Kota Jambi - Sunarto Sunarto; Siti Ubaidah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Mathematics and Physics are subjects that are not only difficult for students but also difficult to do Teacher. To make it easier to understand the material, Geogebra software is used. In the community service, Geogebra training is given to high school teachers in the field of Mathematics and Physics teacher in Jambi City. The training was carried out online involving 10 lecturers and 5 assistants. The training consisted of 4 sessions carried out over 2 days by 31 Mathematics and Physics teachers. Training is divided into 2 classes for more effective. From the results of the training, the ability to use Geogebra increased by 38.05%. The average level of participant satisfaction with the implementation of the research was 4.15 in (a scale 5)